Syndromes in maxillofacial injuries - Farrid Mutatina Shubi; Karpal Singh Sohal; Sira Stanslaus Owibingire (Journal of Medical Sciences, 2019)
A substantial proportion of traumatology involves the maxillofacial region. Injuries to this region are associated with several complications, among them being the different syndromes. These syndromes may arise depending on not only the localization of the initial injury, but also from the treatment itself. This review article aims to bring into the attention of medical community different syndromes that may be associated with maxillofacial injuries.